2008
DOI: 10.1080/03639040701385063
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Aqueous and Organic-Based Films and Coatings of PEGylated Rosin Derivative

Abstract: Rosin was partially esterified with polyethylene glycol 400 and reacted with maleic-anhydride to form an ester-adduct derivative. Derivative and native rosin were characterized for physicochemical properties. Aqueous coating system of derivative was developed by ammonia neutralization method. Organic-based films were produced using acetone. Aqueous and organic-based films were comparatively evaluated. Derivative exhibited an excellent coat-forming ability on spherical-units. Aqueous-based film exhibited very h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
(33 reference statements)
6
16
0
Order By: Relevance
“…The IR spectra of derivatives at 0 hour show C=O stretching ratio at 1690 cm -1 higher than 1721 cm -1 and reduced when the reaction time was increased suggested that the conversion of acid to ester was occurred and increased when increasing reaction time. This is consistent with the previous study [14]. These results suggest that ester group presented in all kinds of rosin-PEG derivatives.…”
Section: G Characterizations Of Rosin Derivativessupporting
confidence: 83%
See 1 more Smart Citation
“…The IR spectra of derivatives at 0 hour show C=O stretching ratio at 1690 cm -1 higher than 1721 cm -1 and reduced when the reaction time was increased suggested that the conversion of acid to ester was occurred and increased when increasing reaction time. This is consistent with the previous study [14]. These results suggest that ester group presented in all kinds of rosin-PEG derivatives.…”
Section: G Characterizations Of Rosin Derivativessupporting
confidence: 83%
“…From this result it can suggest than melting point of derivative was affected from rosin content and melting point of PEG. This result shows consistent with previous study [4], [14], [19]. C-NMR spectra of rosin-PEG 1500 derivatives.…”
Section: International Journal Of Chemical Engineering Andsupporting
confidence: 82%
“…In vitro release studies (Morkhade et al, 2008;Fulzele et al, 2002;Ghosh et al, 2007) The release measurements were performed using 8 stage USP dissolution apparatus-1 (Disso-2000, Lab India). The dissolution parameters (one tablet; 37 ± 0.5°C; 100 rpm; 900 ml of 0.1(N) hydrochloric acid).…”
Section: Disintegration Test (Morkhade Et Al 2008)mentioning
confidence: 99%
“…Our present study is aimed in the preparation of a 25 mg DFS tablet and subsequent development of an optimized film coating formula after properly studying the effects of plasticizer and surfactants for the purpose of coating the tablets (Motola et al, 2001;Morkhade et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of curing time and temperature on the glass transition temperatures of SR30D films is illustrated in Figure 3 such as acid groups [22,23], ionic concentration [24,25], category of counter ion [26][27][28][29], plasticizers [30][31][32] and thermal treatment [25,[33][34][35][36]. Dynamic mechanical analysis After curing at 60°C for 4 hours, there were two endothermic peaks.…”
Section: Glass Transition Temperatures Of Free Filmsmentioning
confidence: 99%